Substrate specific hydrolysis of aromatic and aromatic-aliphatic esters in orchid tissue cultures - Agnieszka Mironowicz; Krystyna Kukułczanka; Antoni Siewiński (Acta Societatis Botanicorum Poloniae, 2014)
We found that tissue cultures of higher plants were able, similarly as microorganisms, to transform low-molecular-weight chemical compounds. In tissue cultures of orchids (Cymbidium 'Saint Pierre' and Dendrobium phalaenopsis) acetates of phenols and aromatic-aliphatic alcohols were hydrolyzed, whereas methyl esters of aromatic and aromatic-aliphatic acids did not undergo this reaction. Acetates of racemic aromatic-aliphatic alcohols were hydrolyzed with distinct enantiospecificity.